Laparoscopic living donor right hemihepatectomy with venous outflow reconstruction using cadaveric common iliac artery allograft: Case report and literature review. Issue 7 (February 2017) - Li, Jiaxin; Huang, Jiwei; Wu, Hong; Zeng, Yong
Abstract: Rationale: With the development of laparoscopic technique, the total laparoscopic living donor right hemihepatectomy (LLDRH) procurement surgery has been successfully performed in many liver transplant centers all over the world, and the number of cases is continuing to increase. We report our case of laparoscopic right graft resection with venous outflow reconstruction using cadaveric common iliac artery allograft in our center and review literatures about total LLDRH surgery. Patient concerns and Diagnoses: A 40-year-old male living donor for right hepatectomy was selected after pretransplant evaluation including laboratory tests, liver volume, anatomy of hepatic vein, artery, portal vein, and bile duct. Living donor liver transplantation surgery was approved by Sichuan Provincial Health Department and the ethics committee of the West China Hospital, Sichuan University. Interventions: Hepatic parenchyma transection was performed by ultrasonic scalpel and Cavitron Ultrasonic Surgical Aspirator (CUSA). Right branch of portal vein, right hepatic artery, right hepatic duct, and right hepatic vein were meticulously dissected. The right hepatic duct was ligated and transected 2 mm far from the bifurcation of common hepatic duct, right hepatic artery, and portal vein were also ligated and transected, the right hepatic vein was transected by laparoscopic linear cutting stapler. The gap between short hepatic veins and right hepatic vein was bridged and reconstructed by cadaveric common iliac artery allograft. Outcomes: The operation time was 480 minutes and warm ischemia time was 4 minutes. Blood loss was 300 mL without blood transfusion. The donor was discharged on postoperative day 7 uneventfully without complications. Literatures about laparoscopic living donor right hemihepatectomy are compared and summarized in table. Lessons: The total laparoscopic living donor right hemihepatectomy is technically feasible and safe in some transplant centers which should have rich open living donor liver transplantation experience and skilled laparoscopic techniques. Venous outflow tract reconstruction is necessary if orifice diameter of short hepatic vein is greater than 0.5 cm on the graft cutting surface.